Anti-tank impact absorption with a reinforced concrete plate design - Polat, Berivan Yilmazer; Savas, Sedat; Polat, Alper (Techno-Press, 2023)
Anti-tank weapons are among the infantry weapons used by the armies of many countries. Anti-tank rockets and explosives such as TNT, generally used for armour piercing, are also frequently used in terrorist attacks. These attacks damage the protection facilities built from reinforced concrete. Rockets or similar explosives' rapid speed and burst temperatures pierce reinforced concrete during strikes, resulting in casualties and damage to crucial strategic structures. This study aimed to devise an economic and applicable reinforced concrete plate that could absorb the impact of anti-tank rockets and Trinitrotoluene (TNT) type explosives. Therefore, 5 different samples, produced from C50 reinforced concrete and 150x150 cm in size, were formed by combining plates of different numbers and thicknesses. Also, a sample, which was a single thick plate, was prepared. In destructive testing, Rocket Propelled Grenade (RPG-7) was used as the anti-tank rocket launcher. As a result of this study, the impact damage was reduced with hollow concrete plate geometries, and recommendations were developed for complete prevention.
Keywords: anti-tank; bomb; concrete; explosion; impact; Rpg-7; shape charge; TNT